2020
DOI: 10.1111/sjop.12670
|View full text |Cite
|
Sign up to set email alerts
|

A trait emotional intelligence perspective on schema modes

Abstract: Schema modes (or modes) are a key concept in the theory underlying schema therapy. Modes have rarely been related to established models of personality traits. The present study thus investigates the associations between trait emotional intelligence (TEI) and 14 modes, and tests a global TEI-mode factorsgeneral psychological distress mediation model. The study draws on self-report data from 173 inpatients from a German clinic for psychosomatic medicine. Global TEI correlated positively with both healthy modes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…The results of the exploratory factor analysis were verified by the results of the confirmatory factor analysis which confirmed the structure of the four factors making the Greek version of the TEIQue-SF valid and reliable. The results of the survey agree with the results of both the questionnaire constructors - Petrides, Pita, and Kokkinaki (2007) -and the results of other studies such as those of Jacobs et al (2021), Di Fabio et al (2016) in Italy, andMerino-Tejedor et al (2018) in Spain. The results of these studies establish and confirm the distribution of the 26 questions across four factors and the contribution of four questions only to the calculation of total emotional intelligence as a personality trait.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the exploratory factor analysis were verified by the results of the confirmatory factor analysis which confirmed the structure of the four factors making the Greek version of the TEIQue-SF valid and reliable. The results of the survey agree with the results of both the questionnaire constructors - Petrides, Pita, and Kokkinaki (2007) -and the results of other studies such as those of Jacobs et al (2021), Di Fabio et al (2016) in Italy, andMerino-Tejedor et al (2018) in Spain. The results of these studies establish and confirm the distribution of the 26 questions across four factors and the contribution of four questions only to the calculation of total emotional intelligence as a personality trait.…”
Section: Discussionsupporting
confidence: 90%
“…The research portrays rather a typical trait EI means from clients receiving mental healthcare in each of the studied countries, as trait EI has consistently been found lowered across various clinical conditions ( Zeidner et al, 2012 ), and more cross-cultural resembles than differences were revealed in our research. Moreover, similar global trait EI means have been reported with relatively large clinical samples (i.e., 200 participants), as this score fell between 4.28 and 4.53 (see Rudenstine and Espinosa, 2018 ; Espinosa and Rudenstine, 2020 ; Jacobs et al, 2021 ), which is congruent with the global trait EI mean of the pooled cross-cultural dataset hereby presented (4.38), a trend that also replicates at the factor-level of trait EI in these studies (Except for Rudenstine and Espinosa, 2018 that did not report factor-level scores), and that deviates from the reported cross-cultural mean of global trait EI in general populations (i.e., 4.85, Pérez-Díaz et al, 2021 ). Therefore, the results support the premise that cultural nuisances in each of the countries affect the distribution of trait EI in clinical participants from different sociodemographic strata, albeit Chileans and Peruvians participants resembled each other more than Spaniards, and that clinical trait EI means are consistently lower than those obtained in general samples.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, trait EI factors mainly showed adequate-to-high reliability (Wellbeing: ω = 0.85, α = 0.85; Self-control: ω = 0.85, α = 0.69; Emotionality: ω = 0.60, α = 0.68; and Sociability: ω = 0.68, α = 0.64); although the values were considerably lower than that of the global trait EI score, which the TEIQue-SF was specifically designed to measure. Moreover, lower than desired (i.e., < 0.70) reliability scores at the factor level (most noticeably for Emotionality and Sociability) had been previously reported in clinical TEIQue-SF samples ( Petrides et al, 2017 ; Jacobs et al, 2021 ; Perez Diaz, 2021 ).…”
Section: Resultsmentioning
confidence: 61%
“…The g‐value factor correlates moderately with the general factor of personality (He & van de Vijver, 2015) and with global TEI. Global TEI is, in turn, a close neighbor of the general factor of personality (van der Linden et al ., 2017) and an indicator of personality functioning (e.g., Jacobs, Wollny, Seidler & Wochatz, 2021). The moderate relation between global TEI and g‐value scores thus implies that the g‐value factor captures qualities that are pertinent to personality functioning: in DSM‐5’s alternative model of personality disorders (APA, 2013), the level of personality functioning concerns disturbances in interpersonal and self‐functioning, and both domains include facets that refer, in part, to value‐guidedness (e.g., utilizing constructive and prosocial internal standards of behavior, setting and pursuing coherent and meaningful goals).…”
Section: Discussionmentioning
confidence: 99%